Decapod Inventory in Mangrove Forest Mangguang Lagoon, Pariaman City, West Sumatera - Lauren Lauren; Ramadhan Sumarmin (Serambi Biologi, 2020)
Decapod Order is one of biological resources which is owned by the marine ecosystem and coastal areas. This research aims to know the species od decapod’s order in the mangrove forest mangguang lagoon, Pariaman City. This research is descriptive conducted on a October to December 2019 in mangrove forest, Pariaman City and the sample identification next to Laboratory of Biologi FMIPA UNP. This research uses VES (Visual Ecounter Survey) at the three station. At each station there are three plot sized 2m x 2m at each plot. In each plot an inventory of species from the Decapoda order is carried out. The results from the order of decapods were found as many as 8 species that is Perisarma guttatum, Uca annulipes, Caridina nilotica, Uca dussumieri, Tmethypocoelis sp., Uca lactea perplexa, Uca triangularis, Varuna sp. The total individu of all species is 243. The highest frequency value is at Uca dussumieri that is 24,5% and the sum of the dominance of all species is 0.2175027.